PENGARUH KECEPATAN ALIR PADA REAKTOR BIOSAND FILTER DALAM INSTALASI PENGOLAHAN AIR BERSIH PADA AIR SUNGAI KARANG MUMUS - Edhi Sarwono; Arzano Rohmahendi; yunianto Setiawan (Mulawarman University Press, 2017)
AbstractThe research about clean water treatment of Karang Mumus river has been done using coagulation reactor, sedimentation flocculation, and biosand filter, so that the water would not causing desease to the citizen around Karang Mumus river who used the water for daily purpose. This research is performed with four treatment variations, those are the flow rate in biosand filter reactor with the variation 0,1 m/hour, 0,2 m/hour, 0,3 m/hour, and 0,4 m/hour. The difference of flow rate in biosand filter reactor will affect the diferrence of contact time in biosand filter reactor. The parameters that is tested in this research are turbidity, organic substance (KMnO4), and total coliform. The result of the laboratory test before and after treatment shows that the highest efficiency on turbidity reduction among each flow rate variations in biosand filter reactor is 0,4 m/hour with the percentage of reduction is 99,45% . The highest efficiency on organic substance (KMnO4) among each flow rate variations is 0,3 m/hour with the percentage of reduction is 33,67%. The highest efficiency on total coliform reduction among each flow rate variations is 0,1 m/hour with the percentage of reduction is 99,21%. Keyword: Biosand Filter, Sedimentation, Flocculation, Koagulation, Karang Mumus River